2001
DOI: 10.1027//1015-5759.17.3.222
|View full text |Cite
|
Sign up to set email alerts
|

The Social Desirability Scale-17 (SDS-17)

Abstract: Summary: Four studies are presented investigating the convergent validity, discriminant validity, and relationship with age of the Social Desirability Scale-17 (SDS-17). As to convergent validity, SDS-17 scores showed correlations between .52 and .85 with other measures of social desirability (Eysenck Personality Questionnaire-Lie Scale, Sets of Four Scale, Marlowe-Crowne Scale). Moreover, scores were highly sensitive to social-desirability-provoking instructions (job-application instruction). Finally, with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
166
1
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 585 publications
(177 citation statements)
references
References 25 publications
4
166
1
6
Order By: Relevance
“…mean MRAI-R553 for Yazbeck et al, 2004). Although a more positive attitude toward inclusion of people with ID was found, it is possible that there may be biased opinions due to the effect of social desirability (Stober, 2001) and that is why many similar previous studies have examined this potential bias (Scior, 2011). Thus, it is recommended that future studies should include a measure of social desirability to assess the validity of participants' responses.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…mean MRAI-R553 for Yazbeck et al, 2004). Although a more positive attitude toward inclusion of people with ID was found, it is possible that there may be biased opinions due to the effect of social desirability (Stober, 2001) and that is why many similar previous studies have examined this potential bias (Scior, 2011). Thus, it is recommended that future studies should include a measure of social desirability to assess the validity of participants' responses.…”
Section: Discussionmentioning
confidence: 93%
“…However, findings of the present survey could guide for constructing another more advanced study in future. Secondly, the responses by participants as to the attitudes toward inclusion of people with ID could be invalid due to social desirability effect (Stober, 2001).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…However, because negative emotions are related to symptom reporting tendencies (Leventhal & Patrick-Miller, 2000;Leventhal et al, 1998), it may be that participants from low negative emotion clusters appear more resilient because they do not report either health symptoms or interference with the activities of daily living--a demand effect. Greater demand or social desirability related to reports of better health (Brosschot & Janssen, 1998;Myers & Reynolds, 2000), has been linked to increasing age (Lawton, Whelihan, & Belsky, 1980;Lewinsohn et al, 1997;Strber, 2001), and is higher among women (C.J. Adams & Krasnoff, 1989;Bardwell & Dimsdale, 2001).…”
Section: Age Cohort Membership Gender and Resiliencymentioning
confidence: 97%
“…25 Therefore, when comparing obesity prevalence rates across socio-demographic groups, objectively measured BMI is preferred. Similarly, the majority of studies on PA are based on self-reported activities that are inevitably subject to response bias owing to the respondent’s blurred memory or tendency to answer questions in a manner that will be viewed favorably by others— labeled as “social desirability tendency.” 26 In the case of self-reported body weight the social desirability bias is manifested as over-reporting height and under-reporting weight and BMI 25 with greater prevalence observed in overweight or obese study participants. 27 …”
mentioning
confidence: 99%